Tropical rainforest palm communities in Madre de Dios in Amazonian Peru - Balslev, Henrik (2016)
We studied palm communities, in particular species-richness and abundance, in the tropical rainforests in southeastern Peru in 54 transects (5×500m) covering an area of 13.5 hectares in flood plain, terra firme, terrace and premontane hills. We found 42 palm species in 18 genera in the transects. Terra firme forest had the highest species richness (38 species) followed by floodplain and premontane hills with 27 species and terrace forests with 26 species. The highest palm abundances were found in premontane hill forest which had 3243 palms per hectare and terra firme forest which had 2968 palms per hectare. The floodplain forests were intermediate in palm abundance with 2647 and the terrace forests had the lowest abundance with 1709 palms per hectare. Intermediate sized palms were the most common being represented by 18 species, while large palms were represented with 16 species. There were only eight species of small palms of which one was acaulescent. Only one species of liana palm was registered. Of the 42 species observed in the 54 transects, 20 were cespitose, 21 solitary and two had colonial growth. Seven species were found 40–320 km outside of their previously known range.